Financial Analysis of Behavioral Health Services in a Pediatric Endocrinology Clinic - Yarbro, Jessica L; Mehlenbeck, Robyn (Journal of pediatric psychology, 2016)
This article addresses a current need in psychological practice by describing a financially feasible model that moves toward integrated care of behavioral health services in a pediatric endocrinology clinic. Financial information (costs and revenue associated with behavioral health services) for the clinic, over an 18-month period (July 2012 to December 2013), was obtained through the hospital's financial department. The clinic meets one half day per week. Over the 18-month period, the behavioral health services generated a net gain of $3661.45 in the favor of the clinic. We determined that the psychologist and clinical psychology residents needed to see a total of four patients per half-day clinic for the clinic to "break-even." We describe one financially feasible way of integrating behavioral health services into a pediatric endocrinology clinic in the hope that this will be generalizable to other medical settings.